The Contribution of Digital Preservation as a Digital Transformation Mechanism within the Scope of the Sustainable Development Objectives of the 2030 Agenda - Pastana Neves, João Paulo; Abbud Grácio, José Carlos; Pomim Valentim, Marta Lígia (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2024)
This study reports how institutions in a contemporary context experiencing significant digital transformations face several challenges to keep their memory alive for the next generations. In this context, digital preservation becomes essential for institutions to preserve their history. Also noteworthy are the Sustainable Development Goals established in the United Nations 2030 Agenda, which focus on sustainable development directly related to digital preservation. This article aims to analyze how humanity should consider Objectives 9, 11, 12 and 13 of the 2030 Agenda, whose objectives are interrelated with the theme of this research work. The methodology used was a bibliographic survey on the Web of Science, Google Scholar and Brapci databases, with a qualitative approach and categorical analysis. It is concluded that the interrelationship of digital preservation through the tool of digital certification in documents in institutions can be used as a mechanism for digital transformation within the scope of the Sustainable Development Goals (SDGs) of the 2030 Agenda.